The Influence Of Government Spending And Amount Of Labor And Inflation On Economic Growth And Labor Absorption In Malinau Regency (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2018)
The purpose of this study was to determine the effect of the direct and indirect effect of government spending, amount of labor and inflation on economic growth and labor absorption in Malinau Regency.Data used in this research is secondary data obtained with a quantitative approach of the Central Statistics Agency Malinau Regency during the years 2004-2014. Hypothesis testing tools using path analysis.The analysis showed that : (1) government spending positive effect and not significant effect on economic growth, (2) amount of labor has negative and not significant effect on economic growth, (3) inflation is positive and significant effect on economic growth, (4) government spending has negative and not significant on labor absorption, (5) amount of labor has negative and not significant on labor absorption, (6) inflation is positive and significant effect on labor absorption, (7) economic growth is negative and not significant on labor absorption, (8) government spending and inflation negative effect on labor absorption through economic growth, while amount of labor has positive effect on labor absorption through economic growth in Malinau.